Pharmacy professionals' views regarding the future of NHS patient medicines helpline services: a multimethod qualitative study - Matt Williams; Abbie Jordan; Jenny Scott; Matthew D. Jones (BMC, 2021)
Abstract Background Patient medicines helpline services (PMHS) have been established at some National Health Service (NHS) hospitals, to provide patients with post-discharge medicines-related support. However, findings suggest that many PMHS are provided sub-optimally due to a lack of resources. This study sought to examine pharmacy professionals' perceptions of the future of PMHS. Methods Participants comprised pharmacy professionals from NHS Trusts in England that provided a PMHS. Invitations to participate in a qualitative survey and then an interview were sent to pharmacy services at all NHS Trusts that provided a PMHS. This resulted in 100 survey participants and 34 interview participants. Data were analysed using Braun and Clarke's inductive reflexive thematic analysis. Results Two themes were generated: Enhancing value for service users and Improving efficiency. Enhancing value for service users identifies pharmacy professionals' suggestions for improving the value of PMHS for service users. These include providing access methods extending beyond the telephone, and providing patients/carers with post-discharge follow-up calls from a pharmacist to offer medicines-related support. Improving efficiency identifies that, in the future, and in line with NHS plans for efficiency and shared resources, PMHS may become centralised or provided by community pharmacies. Centralised services were considered to likely have more resources available to provide a patient medicines information service compared to hospital pharmacies. However, such a change was perceived to only increase efficiency if patient information can be shared between relevant healthcare settings. Conclusions PMHS are perceived by pharmacy professionals as likely to become centralised in the future (i.e., provided regionally/nationally). However, such change is dependent upon the sharing of patients' information between hospitals and the centralised hub/s or pharmacies. To enhance the value of PMHS for service users, providers should consider establishing other methods of access, such as email and video consultation. Considering the uncertainty around the future of PMHS, research should establish the best way to support all patients and carers regarding medicines following hospital discharge.